Genome sequence of Phytomonas françai a Cassava (Manihot esculenta) latex parasite - Kelly, S; Butler, C; Jaskowska, E (American Society for Microbiology, 2017)
Here we report the genome sequence of the cassava (Manihot esculenta) latex parasite Phytomonas françai. P. françai infection is linked with the yield loss disease ‘chochamento de raizes’ (empty roots) in the Unha variety of cassava, a disease characterised by poor root development and chlorosis of the leaves.